Makna Berkat Allah Dalam I Raja-Raja 9:1-9 - Gea, Okta Putra Jaya; Harefa, Yaaro (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
God's blessing is often understood as a gift, so it can make people not responsible for these blessings. In 1 Kings 9:1-9, there is a different teaching about God's blessings. This study aims to explore the meaning of God's blessing in 1 Kings 9:1-9 by using the exegesis method. The research results show that in 1 Kings 9:1-9 there are two meanings of blessing: unconditional and conditional. Because God loved Solomon, He blessed him with his glory and fame as the king of the kingdom of Israel. This is an unconditional blessing. But God also promised other blessings for Solomon and the Israelites. If they were obedient and loyal to Him, the kingdom of Israel would still be victorious. But if they disobey His orders, the kingdom's glory will be destroyed.